2022
DOI: 10.1038/s41598-022-11950-x
|View full text |Cite
|
Sign up to set email alerts
|

Additional treatment of vitamin D for improvement of insulin resistance in non-alcoholic fatty liver disease patients: a systematic review and meta-analysis

Abstract: Insulin resistance provides an important role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Several studies already evaluate vitamin D supplementation for NAFLD patients in relation to insulin resistance. The results obtained still carry conflicting results. This study aimed to evaluate the effect of additional treatment of vitamin D for the improvement of insulin resistance in NAFLD patients. Relevant literatures were obtained from PubMed, Google Scholar, COCHRANE, and Science Direct datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Consistent with a previous meta-analysis, which reported that VD supplementation decreases serum ALT ( 42 ), the present study demonstrated that 25(OH)D 3 was negatively correlated with circulating ALT in patients. To minimize the effect of BMI, we considered BMI as a covariate for multiple logistic regression analysis, aiming to reduce its confounding effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a previous meta-analysis, which reported that VD supplementation decreases serum ALT ( 42 ), the present study demonstrated that 25(OH)D 3 was negatively correlated with circulating ALT in patients. To minimize the effect of BMI, we considered BMI as a covariate for multiple logistic regression analysis, aiming to reduce its confounding effect.…”
Section: Discussionsupporting
confidence: 92%
“…However, a previous cross-sectional study that randomly recruited 789 adult individuals from Portugal has reported that there is no correlation between serum VD and hepatic steatosis ( 41 ). A previous meta-analysis involving eight randomized controlled trials (RCTs) verified that VD supplementation has a protective effect on insulin resistance (IR) and decreases serum alanine aminotransferase (ALT) in NAFLD patients ( 42 ). A prospective cohort study in Korea reported that maintaining an adequate 25(OH)D 3 level (≥30 ng/mL) is associated with decreased incidence of NAFLD ( 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dasarathy et al found that a low vitamin D level can independently predict the severity of NAFLD [ 31 ]. Some clinical trials also demonstrated that vitamin D supplementation has therapeutic effects on patients with NAFLD, including a reduction in liver enzymes, weight, and BMI and an improvement in lipid profile, glycemic control, insulin resistance, and hepatic steatosis and fibrosis [ 32 , 33 , 34 , 35 ]. However, a few studies reported insignificant relationships between vitamin D status and histological severity of NAFLD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given such evidence, randomized controlled trials (RCTs) have found that additional vitamin D treatment may improve insulin resistance, marked by a decrease in Homeostasis Model Assessment Insulin Resistance (HOMA-IR) in patients with NAFLD [ 80 , 81 , 82 ]. These studies were included in a recent meta-analysis that analysed insulin resistance and serum ALT levels [ 83 ]. In a double-blinded, randomised, placebo-controlled trial, vitamin D3 treatment (50,000 IU for 12 weeks) improved HOMA-IR, serum ALT, AST, PCR, and adiponectin but without effect on body weight or serum lipids [ 84 ].…”
Section: Vitamin D In the Chronic Liver Diseasesmentioning
confidence: 99%